Development of a QuEChERS-Based UHPLC-MS/MS Method for Simultaneous Determination of Six Alternaria Toxins in Grapes - Wenbo Guo; Kai Fan; Dongxia Nie; Jiajia Meng; Qingwen Huang; Junhua Yang; Yuanyuan Shen; Emmanuel K. Tangni; Zhihui Zhao; Yongjiang Wu; Zheng Han (Toxins, 2019)
A simple and reliable analytical method for the simultaneous determination of alternariol (AOH), altenuene (ALT), tentoxin (TEN), altenusin (ALS), tenuazonic acid (TeA), and alternariol monomethyl ether (AME) in grapes was developed by ultra-high-performance liquid chromatography⁻tandem mass spectrometry (UHPLC-MS/MS). A modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) procedure with the extraction by acetonitrile and purification by sodium chloride (0.5 g) and anhydrous magnesium sulfate (0.5 g) was established to recover the six Alternaria toxins. After validation by determining the linearity (R2 > 0.99), recovery (77.8⁻101.6%), sensitivity (limit of detection in the range of 0.03⁻0.21 μg kg−1, and limit of quantification in the range of 0.09⁻0.48 μg kg−1), and precision (relative standard deviation (RSD) ≤ 12.9%), the analytical method was successfully applied to reveal the contamination state of Alternaria toxins in grapes. Among 56 grape samples, 40 (incidence of 71.4%) were contaminated with Alternaria toxins. TEN was the most frequently found mycotoxin (37.5%), with a concentration range of 0.10⁻1.64 μg kg−1, followed by TeA (28.6%) and AOH (26.8%). ALT (10.7%), AME (3.6%), and ALS (5.4%) were also detected in some samples. To the best of our knowledge, this is the first report about the Alternaria toxins contamination in grapes in China.